A follow-up study on the etiology and occurence of ameloblastoma among filipinos from 1980 to 1989 in selected Metro Manila Hospitals - De Guia, Ma. Jovita L.
In this study, recorded cases of ameloblastoma from several hospitals were reviewed and data gathered as to the disease's foremost etiology, incidence and prevalence and the age of the individuals affected by the disease among Filipinos in a period of ten years. The results indicated that trauma due to tooth extraction remains the foremost etiology and most of those affected were still in the twenty to forty year age range. There's also a significant number of those affected in the below 20 year age range and there is a general trend of increase in a period of ten years.